High-light-transmittance ethylene copolymer and application thereof

By developing a high light transmittance ethylene copolymer with an olefin with an odd carbon atom of more than 4 and an odd number as a comonomer, the problems of high α-olefin usage and high cost of odd carbon α-olefins in POE materials are solved, and the effects of high light transmittance and low production cost are achieved.

CN119899304AActive Publication Date: 2025-04-29ZHEJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510115290.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-29
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The high amount of α-olefins in existing POE materials leads to high production costs, and the high cost of odd carbon α-olefins, making it difficult to meet the needs of large-scale commercial production.

Method used

A high light transmittance ethylene copolymer was developed, using olefins with carbon atoms greater than 4 and odd numbers as comonomers, prepared by solution polymerization process, using metallocene catalysts, and controlling the molar content of the [EXX] fragments between 0.1-5.0 mol % to achieve low cost and efficient utilization of odd numbers of carbon alpha-olefins.

Benefits of technology

The dual advantages of high light transmittance and low comonomer insertion rate are achieved, with a light transmittance of no less than 90%, and the odd carbon α-olefin insertion rate is low, which significantly reduces production costs and enhances market competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899304A_ABST
    Figure CN119899304A_ABST
Patent Text Reader

Abstract

The invention discloses a high-light-transmittance ethylene copolymer and application thereof. The molar content of the second olefin X in the copolymer accounts for 1.8-9.9 mol%, the second olefin X is an odd number of carbon atoms larger than 4, the molar content of the [EXX] segment accounts for 0.1-5.0 mol% of the total ternary segment content, the molar content of the [EEE] segment accounts for 70-90 mol% of the total ternary segment content, the molar content of the [EXE] segment accounts for 2.0-8.0 mol% of the total ternary segment content, and the molar content of the [EXE] segment accounts for 0.1-5.0 mol% of the total ternary segment content. The molar content of the [XEE] fragment accounts for 0.5-3.0 mol% of the total ternary fragment content, and the molar content of the [XEX] fragment accounts for 3.5-10.0 mol% of the total ternary fragment content. In the copolymer, when the molar content of [EXX] fragments accounts for 0.15 mol% of the total ternary fragment content, the light transmittance of a copolymer film material subjected to hot press molding is not lower than 90%, and extremely high second olefin X atom economy is shown. The copolymer can be applied to the fields of photovoltaic adhesive films, polyolefin material toughening, wire and cable, engineering plastic modification and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyolefin material, in particular to an ethylene copolymer with high light transmittance and application thereof. Background Art

[0002] Polyolefin materials with high light transmittance, such as polyethylene elastomer (POE), ethylene-vinyl acetate copolymer (EVA), cycloolefin copolymer (COC), polymethyl methacrylate (PMMA), etc., are widely used in photovoltaic encapsulation, optical lenses, packaging materials, medical devices and other fields. Taking POE material as an example, due to its excellent anti-PID performance, high water vapor barrier performance, weather resistance, and high electrical insulation performance, it is gradually replacing EVA material in the field of photovoltaic film. However, POE material is relatively expensive, resulting in high cost of POE photovoltaic film, which is mainly due to the high price of its comonomer α-olefin, the long solution production process and high cost. It can be seen that how to reduce the amount of α-olefin in POE material and reduce production costs while maintaining the high light transmittance of POE material is crucial to POE material.

[0003] In the existing POE production, the α-olefin comonomers are all even-numbered carbons, mainly 1-butene, 1-hexene and 1-octene. This is mainly due to the high cost of odd-numbered carbon α-olefins, and there is no low-cost supply of odd-numbered carbon α-olefins, which is difficult to meet the needs of large-scale commercial production. At present, domestic coal chemical enterprises have made breakthroughs in the production technology of coal-to-olefins and can produce high-quality coal-based α-olefins. Coal-based α-olefins have olefins of different carbon numbers (C5-C16), and how to achieve efficient utilization of odd-numbered carbon olefins is imminent. CN1328581A proposes a polymer obtained from a first olefin having less than 4 carbon atoms and a second olefin having more than 5 and an odd number of carbon atoms. The molar ratio of the first olefin to the second olefin in the polymer ranges from 90:10 to 99.9:0.1; a method for preparing the polymer is also provided, which uses a Ziegler-Natta catalyst or a catalyst system to react the first olefin and the second olefin in one or more reaction zones, and the pressure in the reaction zone is between atmospheric pressure and 200kg / cm 2 The temperature is between ambient temperature and 300°C, and the density of the polymer is between 0.910-0.950 g / cm 3Between. The polymer density in this invention belongs to the range of LLDPE, MDPE and HDPE, does not include the density range of POE, and the catalyst used is a Ziegler-Natta catalyst. In addition, CN118271498A provides an optical POE material, a preparation method and an application thereof, in which the sequence structure of the optical POE material contains less than 80% of the ternary sequence EEE, more than 10% of the EXE+XEX sequence, and a comonomer molar insertion rate of 10% to 20%. The optical POE material provided by this invention has the characteristics of high transmittance and low melting point, and is very suitable for use in the field of laser welding. The comonomer used in this invention is still an even-numbered carbon α-olefin, selected from one or more of butene, hexene and octene.

[0004] Therefore, how to develop a POE material with both high light transmittance and low comonomer insertion rate is extremely challenging and is crucial to improving the added value and market competitiveness of POE products. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a high light transmittance ethylene copolymer and its application. The copolymer provided by the present invention has the dual advantages of small α-olefin insertion amount and high light transmittance.

[0006] According to one object of the present invention, the present invention provides a copolymer of ethylene and a second olefin, wherein the molar content of the second olefin X in the copolymer accounts for 1.8-9.9 mol%, and the second olefin X is an olefin having an odd number of carbon atoms greater than 4, and in the copolymer, the molar content of the [EXX] fragment accounts for 0.1-5.0 mol% of the total ternary fragment content. In the copolymer of the present invention, the ternary fragment is divided into six types: [EEE], [EXE], [XEE], [EXX], [XEX], and [XXX], and E represents an ethylene unit. In the present invention, the arrangement direction of the ternary fragment is not distinguished, so the [EXX] fragment and the [XXE] fragment are considered to be the same fragment, and are both represented by the [EXX] fragment; the [XEE] fragment and the [EEX] fragment are also considered to be the same fragment, and are both represented by the [XEE] fragment. In the art, the content of each ternary fragment can be obtained by nuclear magnetic carbon spectrum testing, which is a well-known method in the industry.

[0007] According to a preferred embodiment of the present invention, in the copolymer, the molar content of the [EEE] fragment accounts for 70-90 mol% of the total ternary fragment content, the molar content of the [EXE] fragment accounts for 2.0-8.0 mol% of the total ternary fragment content, the molar content of the [XEE] fragment accounts for 0.5-3.0 mol% of the total ternary fragment content, and the molar content of the [XEX] fragment accounts for 3.5-10.0 mol% of the total ternary fragment content.

[0008] According to a preferred embodiment of the present invention, in the copolymer, the second olefin X is selected from one or more of 1-pentene, 1-heptene, 1-nonene and 1-undecene.

[0009] According to a preferred embodiment of the present invention, the weight average molecular weight of the copolymer is 50000-300000 g / mol, the molecular weight distribution is 1.5-8.0, the melting point is 60-100°C, and the density is 0.868-0.898 g / cm 3 , tensile strength is 5-50MPa.

[0010] The present invention also provides a method for preparing the copolymer, wherein the copolymer is prepared by solution polymerization, the catalyst used for polymerization is a metallocene catalyst, the central metal element M of the metallocene catalyst is connected to the N atom, the C atom and the Cl atom, and the bite angle of the central metal element M is 105-115°. The polymerization temperature is 100-180°C, and the polymerization pressure is 1.8-5.0MPa.

[0011] The polymerization solution is selected from one or more of n-pentane, isopentane, n-hexane, cyclohexane, n-heptane, 2-methylhexane, 3-methylhexane, isoparaffin Isopar C and isoparaffin Isopar E.

[0012] The metallocene catalyst is selected from one or more of a bridged metallocene catalyst, a non-bridged metallocene catalyst, and a constrained geometry catalyst, and the cocatalyst is selected from one or more of methylaluminoxane, modified methylaluminoxane, tri(pentafluorophenyl)borane, borates, triethylaluminum, triisobutylaluminum, and trihexylaluminum.

[0013] Preferably, when the molar content of the [EXX] segment in the copolymer accounts for 0.15 mol% of the total ternary segment content, the light transmittance of the copolymer film after hot pressing is not less than 90%, preferably not less than 90.5%.

[0014] The present invention also provides an application of the copolymer, which can be used to prepare photovoltaic adhesive films, polyolefin material toughening agents, wires and cables, and engineering plastic modifiers, and has a wide range of applications.

[0015] The present invention has the following outstanding gain effects:

[0016] (1) In the copolymer of the present invention, the second olefin X is an α-olefin with an odd number of carbon atoms and greater than 4 carbon atoms (preferably one or more of 1-pentene, 1-heptene, 1-nonene, and 1-undecene). During the crystallization process of the copolymer molecular chain, the branched structure with an odd number of carbon atoms is not easy to crystallize. Compared with the branched structure with an even number of carbon atoms, the crystallinity of the α-olefin copolymer with an odd number of carbon atoms is relatively low. It is well known that the light transmittance of the copolymer is closely related to the content of the amorphous region. The higher the content of the amorphous region, the higher the light transmittance. Therefore, the ethylene copolymer with an odd number of carbon branched structure has a higher light transmittance than the ethylene copolymer with an even number of carbon branched structure.

[0017] (2) Through experimental research, it was found that in the copolymer of the present invention, when the insertion rate of the second olefin X reaches 2.5 mol%, the obtained ethylene and odd-numbered carbon α-olefin copolymer has an extremely high light transmittance of more than 90.5%, and the copolymer density is about 0.895 g / cm 3 Compared with lower density ethylene and 1-octene copolymers, such as Dow Chemical Engage 8003 grade POE, the density is about 0.885g / cm 3 , the transmittance is only 89.0%, while the 1-octene insertion rate of Engage 8003 brand POE is as high as over 20wt%. It can be seen that the ethylene and odd-carbon α-olefin copolymers of the present invention only require extremely low odd-carbon α-olefin insertion rates to achieve the requirements of high transmittance, and have extremely high α-olefin atom economy. The price of α-olefins is much higher than the price of ethylene, which can significantly improve the market competitiveness of the ethylene and odd-carbon α-olefin copolymers. When the molar content of the copolymer [EXX] segment accounts for 0.15 mol% of the total ternary segment content, the transmittance of the copolymer film after hot pressing is not less than 90%.

[0018] (3) Since the odd-numbered α-olefin insertion rate requirement in the ethylene and odd-numbered α-olefin copolymer of the present invention is relatively low, it has a higher melting point and tensile strength. A higher melting point can improve the processing performance of the copolymer when toughening and modifying general-purpose plastics or engineering plastics. A higher tensile strength can improve the tensile strength and application range of the modified material after modifying general-purpose plastics or engineering plastics. Therefore, this ethylene and odd-numbered α-olefin copolymer is not only suitable for photovoltaic films, medical packaging and other fields with high light transmittance requirements, but also suitable for plastic modification and toughening fields with high mechanical properties requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the NMR carbon spectrum of ethylene and odd-numbered α-olefin copolymer A (Example 1).

[0020] Figure 2 It is the stress-strain curve of ethylene and α-olefin copolymer. DETAILED DESCRIPTION

[0021] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0022] The following methods are used to test the structure or properties of the ethylene and α-olefin copolymers produced in the examples described:

[0023] High temperature gel permeation chromatography (GPC) was used to test the weight average molecular weight and molecular weight distribution of the copolymer.

[0024] A gradient densitometer was used to test the density of the copolymers.

[0025] Nuclear magnetic resonance spectroscopy was used to test the insertion rate of α-olefin in the copolymer.

[0026] Universal testing machine was used to test the tensile strength of copolymers.

[0027] Differential scanning calorimetry (DSC) was used to measure the melting point and melting enthalpy of the copolymers.

[0028] The haze tester is used to test the light transmittance of copolymers.

[0029] Example 1

[0030] In a 10L reactor that has been dehydrated and deoxygenated, 5L of n-hexane solvent, 1.4L of the second olefin 1-heptene, 10mmol of cocatalyst methylaluminoxane and 18μmol of tri(pentafluorophenyl)borane were successively added, ethylene was added until the pressure in the reactor reached 3MPa, the temperature was raised and stabilized at 130°C, and finally 16μmol of metallocene CGC catalyst (CAS135072-61-6) was injected and the pressure in the reactor was kept constant at 3MPa. After reacting for 10min, the material was discharged, and the copolymer A was collected and dried and weighed. The physical property characterization results of copolymer A are shown in Table 1, and the nuclear magnetic carbon spectrum characterization results are shown in Table 2.

[0031] Example 2

[0032] In a 10L reactor that has been dehydrated and deoxygenated, 5.5L of cyclohexane solvent, 2.0L of the second olefin 1-heptene, and 8mmol of the co-catalyst modified methylaluminoxane are successively added, ethylene is charged until the pressure in the reactor reaches 3MPa, the temperature is raised and stabilized at 150°C, and finally 14μmol of metallocene catalyst (CAS132510-07-7) is injected and the pressure in the reactor is kept constant at 3MPa. After reacting for 10min, the material is discharged, and the copolymer B is collected and dried and weighed. The physical property characterization results of copolymer B are shown in Table 1, and the nuclear magnetic carbon spectrum characterization results are shown in Table 2.

[0033] Example 3

[0034] In a 10L reactor that has been dehydrated and deoxygenated, 6L of isoparaffin Isopar E solvent, 2.5L of the second olefin 1-heptene, and 8mmol of the co-catalyst modified methylaluminoxane were successively added, ethylene was added until the pressure in the reactor reached 4MPa, the temperature was raised and stabilized at 120°C, and finally 15μmol of metallocene catalyst (CAS100163-29-9) was injected and the pressure in the reactor was kept constant at 4MPa. After reacting for 10min, the material was discharged, and the copolymer C was collected and dried and weighed. The physical property characterization results of copolymer C are shown in Table 1, and the nuclear magnetic carbon spectrum characterization results are shown in Table 2.

[0035] Example 4

[0036] In a 10L reactor that has been dehydrated and deoxygenated, 5L of n-hexane solvent, 1.0L of the second olefin 1-heptene, 0.8L of the second olefin 1-pentene, 1mmol of triisobutylaluminum as a cocatalyst, and 18μmol of tri(pentafluorophenyl)borane were successively added, ethylene was added until the pressure in the reactor reached 3MPa, the temperature was raised and stabilized at 140°C, and finally 15μmol of metallocene catalyst (CAS135072-61-6) was injected and the pressure in the reactor was kept constant at 3MPa. After reacting for 10min, the material was discharged, and the copolymer D was collected and dried and weighed. The physical property characterization results of copolymer D are shown in Table 1, and the nuclear magnetic carbon spectrum characterization results are shown in Table 2.

[0037] Comparative Example 1

[0038] In a 10L reactor that had been dehydrated and deoxygenated, 5L of n-hexane solvent, 1.4L of 1-octene, 10mmol of cocatalyst methylaluminoxane and 18μmol of tri(pentafluorophenyl)borane were successively added, ethylene was added until the pressure in the reactor reached 3MPa, the temperature was raised and stabilized at 130°C, and finally 16μmol of metallocene CGC catalyst (CAS 135072-61-6) was injected and the pressure in the reactor was kept constant at 3MPa. After reacting for 10min, the material was discharged, and the copolymer E was collected and dried and weighed. The physical property characterization results of copolymer E are shown in Table 1, and the nuclear magnetic carbon spectrum characterization results are shown in Table 2.

[0039] Comparative Example 2

[0040] In a 10L reactor that has been dehydrated and deoxygenated, 5L of n-hexane solvent, 1.4L of the second olefin 1-heptene, and 30mmol of triethylaluminum as a cocatalyst are successively added, ethylene is added until the pressure in the reactor reaches 3MPa, the temperature is raised and stabilized at 105°C, and finally 1g of supported Ziegler-Natta catalyst A (prepared according to the following method) is added, and the pressure in the reactor is kept constant at 3MPa. After reacting for 10 minutes, the material is discharged, and the copolymer F is collected and dried and weighed. The physical property characterization results of copolymer F are shown in Table 1, and the nuclear magnetic carbon spectrum characterization results are shown in Table 2.

[0041] The preparation method of supported Ziegler-Natta catalyst A is as follows, which is the preparation method of catalyst A in Example 1 of comparative patent CN1328581A:

[0042] In a 250 mL flask equipped with a reflux condenser and a stirring device, 2 g of magnesium chloride with a total water content of 1.5% (mass percent) was suspended in 60 mL of highly purified hexane. 4 mL of a 1:1 molar mixture of diamyl ether and ethanol was added to the flask and the mixture was stirred for 3 hours under reflux conditions. The mixture was cooled to ambient temperature and 10 g of triethylaluminum was added dropwise to avoid excessive heat of formation. The obtained slurry was cooled to room temperature under stirring conditions and then washed 12 times with 50 mL of hexane each time to obtain a slurry containing an activated support.

[0043] To the slurry containing the activated support was added 2 mL of a 1:1 molar mixture of ethanol and 1-nonanol and the slurry was stirred at ambient temperature for 3 hours. Then 15 mL of TiCl4 was added and the mixture was stirred at reflux for 2 hours. After cooling, the slurry was washed 10 times with 50 mL of hexane each time and then dried.

[0044] Comparative Example 3

[0045] In a 10L reactor that has been dehydrated and deoxygenated, 5L of n-hexane solvent, 1.0L of the second olefin 1-heptene, 0.8L of the second olefin 1-pentene, and 30mmol of the cocatalyst triethylaluminum were successively added, ethylene was added until the pressure in the reactor reached 12MPa, the temperature was raised and stabilized at 230°C, and finally 1g of Ziegler-Natta catalyst B (titanium tetrachloride and vanadium trichloride in catalyst B were in a ratio of 2:8) was added, and the pressure in the reactor was kept constant at 12MPa. After reacting for 10min, the material was discharged, and the copolymer G was collected and dried and weighed. The physical property characterization results of copolymer G are shown in Table 1, and the nuclear magnetic carbon spectrum characterization results are shown in Table 2.

[0046] Comparative Example 4

[0047] In a 10L reactor that has been dehydrated and deoxygenated, 5L of n-hexane solvent, 2.0L of the second olefin 1-heptene, and 10mmol of the co-catalyst methylaluminoxane are successively added, ethylene is charged until the pressure in the reactor reaches 3MPa, the temperature is raised and stabilized at 130°C, and finally 16μmol of the metallocene catalyst dichlorotitanocene (CAS1271-19-8) is injected and the pressure in the reactor is kept constant at 3MPa. After reacting for 10min, the material is discharged, and the copolymer H is collected and dried and weighed. The physical property characterization results of copolymer H are shown in Table 1, and the nuclear magnetic carbon spectrum characterization results are shown in Table 2. In the dichlorotitanocene (CAS 1271-19-8) molecule, the bond angle between the titanium atom and the cyclopentadienyl ligand is close to 120°.

[0048] Table 1 Characterization results of copolymer AH

[0049]

[0050] Table 2 Characterization results of NMR carbon spectrum of copolymer AH

[0051]

[0052] From Table 1 and Table 2, it can be seen that under the same polymerization conditions, copolymer A has a lower melting point and lower melting enthalpy than copolymer E, indicating that the branched structure of odd-numbered carbon atoms is not prone to crystallization. The light transmittance of copolymer A is as high as 90.7%, which is higher than the light transmittance of copolymer E (89.6%). Figure 1 According to the NMR carbon spectrum shown in Figure 2, the insertion rate of 1-heptene in copolymer A is only 3.51 mol%, which is about 11.31 wt% by weight, while the insertion rate of 1-octene in copolymer E is 3.68 mol%, which is about 13.28 wt% by weight. It can be seen that using odd-numbered carbon 1-heptene as a comonomer has higher atom economy in POE production. In addition, the tensile strength of copolymer A can reach 26.8 MPa, which is much higher than 18.9 MPa of copolymer E (see Figure 2). Figure 2 ).

[0053] Copolymer F and copolymer G are prepared by supported and non-supported Ziegler-Natta catalysts, and the second olefin X insertion rate of copolymer F is 1.11mol%, wherein the [EXX] fragment content is 0.47mol%, but the [EXE] and [XEX] fragment contents are only 0.90mol% and 0.02mol%. Therefore, the [EEE] fragment content in copolymer F is as high as 96.42mol%, resulting in a transmittance of copolymer F of only 32.6%. Due to the multi-active center characteristics of supported Ziegler-Natta catalysts, even if the content of the second olefin X in the polymerization system is increased, it is difficult to achieve the improvement of the second olefin X insertion rate. The preparation of copolymer G is under 230°C and 12MPa conditions (i.e. Sclairtech solution polymerization process), and the second olefin X insertion rate in the copolymer G obtained under the process conditions of Comparative Example 3 is 1.77mol%, wherein the [EXX] fragment content is 0.51mol%, but the [EXE] and [XEX] fragment contents are only 1.52mol% and 0.04mol%. Therefore, the content of [EEE] fragment in copolymer G is as high as 94.09 mol%, resulting in a transmittance of copolymer G of only 35.1%. Since the production process uses a non-supported Ziegler-Natta catalyst, even if the amount of the second olefin X is increased, a density lower than 0.918 g / cm 3It can be seen that both the supported and unsupported Ziegler-Natta catalysts cannot produce high-transmittance ethylene copolymers whose ternary sequence fragment content meets the ratio range described in the patent of the present invention.

[0054] The copolymer H is prepared by solution polymerization process, and the catalyst is dichlorodiphenyltitanate (CAS1271-19-8). The bond angle between the titanium atom and the cyclopentadienyl ligand in the metallocene catalyst molecule is close to 120°, which is much higher than the metal bite angle 105-115° of the restricted geometry CGC metallocene catalyst center used in Examples 1-4. Therefore, the contents of [EXE], [EXX], [XEX], [XEE] and [EEE] fragments in the copolymer H are 4.29mol%, 0.08mol%, 1.57mol%, 10.60mol% and 83.46mol%, respectively. The second olefin X is concentrated in the [XEE] fragment, which is much higher than the [XEE] fragment content in Examples 1-4, the [XEX] fragment content is low, and the [EXX] fragment content is only 0.08mol%, resulting in a light transmittance of the copolymer H of only 80.1%. Due to the large bite angle of the central metal of the dichlorotitanium catalyst, the content of [EXX] and [XEX] fragments is relatively low, which seriously affects the transmittance of the copolymer.

[0055] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A copolymer of ethylene and a second olefin, characterized in that: The molar content of the second olefin X in the copolymer is 1.8-9.9 mol%, and the second olefin X is an olefin with an odd number of carbon atoms greater than 4. In the copolymer, the molar content of the [EXX] segment accounts for 0.1-5.0 mol% of the total ternary segment content; the ternary segments are divided into six types: [EEE], [EXE], [XEE], [EXX], [XEX], and [XXX], wherein E represents an ethylene unit.

2. The copolymer according to claim 1, characterized in that The molar content of [EEE] fragment accounts for 70-90 mol% of the total ternary fragment content, the molar content of [EXE] fragment accounts for 2.0-8.0 mol% of the total ternary fragment content, the molar content of [XEE] fragment accounts for 0.5-3.0 mol% of the total ternary fragment content, and the molar content of [XEX] fragment accounts for 3.5-10.0 mol% of the total ternary fragment content.

3. The copolymer according to claim 1, characterized in that The second olefin X is selected from one or more of 1-pentene, 1-heptene, 1-nonene and 1-undecene.

4. The copolymer according to claim 1, characterized in that The weight average molecular weight of the copolymer is 50000-300000 g / mol, the molecular weight distribution is 1.5-8.0, the melting point is 60-100°C, and the density is 0.868-0.898 g / cm 3 , tensile strength is 5-50MPa.

5. A method for preparing the copolymer according to claim 1, characterized in that: The copolymer is prepared by solution polymerization. The catalyst used for the polymerization is a metallocene catalyst. The central metal element M of the metallocene catalyst is connected with the N atom, the C atom and the Cl atom. The bite angle of the central metal element M is 105-115 degrees.

6. The method according to claim 5, characterized in that The polymerization temperature is 100-180° C., the polymerization pressure is 1.8-5.0 MPa, and the mass of the second olefin X in the solution accounts for 12.0-40.0 wt % of the total mass of the solution.

7. The method according to claim 5, characterized in that The polymerization solution is selected from one or more of n-pentane, isopentane, n-hexane, cyclohexane, n-heptane, 2-methylhexane, 3-methylhexane, isoparaffin Isopar C and isoparaffin Isopar E.

8. The method according to claim 5, characterized in that The metallocene catalyst is selected from one or more of a bridged metallocene catalyst, a non-bridged metallocene catalyst, and a constrained geometry catalyst, and the cocatalyst is selected from one or more of methylaluminoxane, modified methylaluminoxane, tri(pentafluorophenyl)borane, borates, triethylaluminum, triisobutylaluminum, and trihexylaluminum.

9. Use of the copolymer according to any one of claims 1 to 4, or the copolymer prepared by the method according to any one of claims 5 to 8 in the preparation of photovoltaic adhesive films, polyolefin material toughening agents, wires and cables, or engineering plastic modifiers.

10. The use according to claim 9, characterized in that: When the molar content of the copolymer [EXX] segment accounts for 0.15 mol% of the total ternary segment content, the light transmittance of the copolymer film after hot pressing molding is not less than 90%.

Citation Information

Patent Citations

  • Polymerization of copolymers of ethylene / propylene with higher olefins

    CN1328581A

  • Preparation method of ethylene / alpha-olefin copolymer

    CN103936909A

  • High-toughness polyolefin film and preparation method thereof

    CN116656036A

  • High light transmittance ethylene / alpha-olefin copolymers

    CN116789884A

  • Composition for Encapsulant Film Comprising Ethylene / Alpha-Olefin Copolymer and Encapsulant Film Comprising the Same

    US20220282010A1